Characterization of Photosynthetic Phenotypes and Chloroplast Ultrastructural Changes of Soybean (Glycine max) in Response to Elevated Air Temperatures - Herritt, Matthew T.; Fritschi, Felix B. (Frontiers in Plant Science, 2020)
Heat stress negatively affects photosynthesis in crop plants. Chlorophyll fluorescence provides information about the efficiency of the light-dependent reactions of photosynthesis and can be measured non-destructively and rapidly. Four soybean (Glycine max) genotypes were grown in controlled environments at 28/20°C (control), followed by imposition of control, 38/28 °C, and 45/28 °C day/night temperature regimes for seven days. Coordinated chlorophyll fluorescence, gas exchange, and chloroplast ultrastructure measurements were conducted over the course of the seven-day temperature treatments and revealed contrasting responses among the different genotypes. Although generally similar, the extent of the impact of elevated temperatures on net photosynthesis differed among genotypes. Despite dramatic effects on photosynthetic light reactions, net photosynthetic rates were not reduced by exposure to 45 °C on the 1st day of treatment imposition. Temporal dynamics of light reaction characteristics over the course of the seven-day heat-wave simulation revealed distinct responses among the genotypes. Similarly, chloroplast ultrastructure examination identified contrasting responses of DT97-4290 and PI603166, particularly with respect to starch characteristics. These changes were positively associated with differences in the percent area of chloroplasts that were occupied by starch grains. The starch dynamics were coordinated with alterations in chlorophyll fluorescence and gas exchange phenotypes. Elevated temperature increased number and size of starch grains on the 1st day of DT97-4290 which was coordinated with increased minimum chlorophyll fluorescence (F0) and reduced leaf net CO2 assimilation (A). Whereas on the 7th day the elevated temperature treatment showed reduced numbers and sizes of starch grains in chloroplasts and was coordinated with similar levels of F0 and A to the control treatment. Unlike starch dynamics of PI603166 which elevated temperature had little effect on. The genotypic differences in photosynthetic and chloroplast ultrastructure responses to elevated temperatures identified here are of interest for the development of more tolerant soybean cultivars and to facilitate the dissection of molecular mechanisms underpinning heat stress tolerance of soybean photosynthesis.